Estudo do efeito de diferentes protocolos fisioterapêuticos no tratamento da osteoartrite de joelho - Pereira, Fernando Garbi [UNESP] (2014)
Introduction: Osteoarthritis (OA), a chronic degenerative disease of high prevalence, is the most common joint disorder, affecting 6% to 12% of the adult population and more than a third of people over 65 years old. Objective: To compare the effects of different physiotherapy protocols in the treatment of knee osteoarthritis in the elderly. Study Design: A randomized study, controlled, prospective, analytical, parallel, open-label. Subjects: 49 participants aged 60 years and over, with clinical OA of the knee. Methods: Patients were randomized into one of three groups: Aquatic Physiotherapy (GI), Land Physiotherapy (GII) and Control Group (GIII). Exercise programs were performed twice weekly for a period of two months. All participants were assessed before and after program implementation (six-minute walk test (6MWT), body mass index (BMI), Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and Timed up & Go Test (TUGT). Results: At the end of the study, 45 patients remained. After analyzing the data, we found a statistically significant improvement of all variables in GI and GII when compared to GIII (p <0.05), while among GI and GII there were no significant differences. (p> 0.05). Conclusion: The protocols of land and aquatic therapy resulted in significant improvement in symptoms of pain, stiffness, physical activity, reducing the risk of falls and improves the functional capacity of older adults with knee OA